Self-repairing epoxy coating loaded with corrosion inhibitor ZIF-8 particles and preparation method of self-repairing epoxy coating

By adding the anti-corrosion filler of the ZIF-8 particles to the ZIF-8 particles to the epoxy coating, the problem of forming micropores and micro-cracks in the process of solidification and use of epoxy coatings, realizing the self-repair and use of coating Life extension.

CN119331481APending Publication Date: 2025-01-21SOUTHWEST TECHNICAL ENGINEERING RESEARCH INSTITUTE OF CHINA SOUTH IND GROUP +1

Patent Information

Application Number
CN202411447757.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Epoxy coatings are prone to micropores and microcracks during curing and use, resulting in a shorter service life.

Method used

A self-healing epoxy coating loaded with corrosion inhibitor ZIF-8 particles is used. By adding an anti-corrosion filler with a zeolite imidazole ester framework loaded with benzotriazole in the coating, the porous structure of ZIF-8 and benzotriazole are used. The corrosion inhibition performance of nitrogen azole enables self-healing of the coating.

Benefits of technology

The service life of the epoxy coating is extended, the protective performance and self-healing effect of the coating are improved, and the preparation method is simple and convenient for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331481A_ABST
    Figure CN119331481A_ABST
Patent Text Reader

Abstract

The invention relates to a self-repairing epoxy coating loaded with corrosion inhibitor ZIF-8 particles and a preparation method of the self-repairing epoxy coating. The coating adopts an anticorrosive filler; the preparation method comprises the following steps: dissolving benzotriazole in methanol to obtain a benzotriazole solution, and dissolving a zinc source in methanol to obtain a zinc source solution; the preparation method comprises the following steps: adding 2-methylimidazole into methanol to obtain a 2-methylimidazole solution; adding a benzotriazole solution into the zinc source solution to obtain a mixed solution, adding a 2-methylimidazole solution into the mixed solution, stirring, centrifuging, washing and drying to obtain the anticorrosive filler. The corrosion inhibitor is high in loading capacity and can be controllably released after corrosion reaction, and the self-repairing effect of the coating is excellent; the BTA (at) ZIF-8 particles are high in pyrolysis temperature, so that the problem of failure in advance is avoided; the compatibility of BTA and ZIF-8 and the EP coating is good, the corrosion inhibition efficiency of BTA is high, the self-repairing effect can be observed within 48 h, BTA and ZIF-8 can be easily dispersed in the coating, and therefore the corrosion inhibition efficiency of the prepared coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of self-repairing epoxy coatings, and specifically relates to a self-repairing epoxy coating loaded with corrosion inhibitor ZIF-8 particles and a preparation method thereof. Background Art

[0002] Epoxy coatings have excellent anti-corrosion properties, electrical insulation properties, and mechanical strength, and are widely used in steel structures, concrete surface coatings, corrosion-resistant tank linings, and other special functional requirements in coastal, offshore, and chemically corrosive environments. Generally speaking, epoxy coatings can serve as a physical barrier between corrosive media and metal surfaces in marine environments to delay metal corrosion. However, epoxy coatings will form micropores and microcracks during curing and use, which will reduce the service life of epoxy coatings.

[0003] Therefore, it is necessary to develop a material that can solve the technical problem of micropores and microcracks formed in the above-mentioned epoxy coating during curing and use, so as to extend the service life of the epoxy coating. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a self-repairing epoxy coating loaded with corrosion inhibitor ZIF-8 particles and a preparation method thereof, so as to extend the service life of the epoxy coating.

[0005] To achieve the above-mentioned purpose, the scheme of the present invention is as follows: In the first aspect, the present invention provides a self-healing epoxy coating loaded with corrosion inhibitor ZIF-8 particles, including an anti-corrosion filler added to the coating raw material, the anti-corrosion filler includes a zeolite imidazole ester skeleton loaded with benzotriazole, and the average particle size of the zeolite imidazole ester skeleton loaded with benzotriazole is 1-1.5μm.

[0006] Optionally, the zeolite imidazole ester framework loaded with benzotriazole is spherical.

[0007] Furthermore, the method for preparing the self-repairing epoxy coating comprises the following steps: S1. dissolving benzotriazole in methanol to obtain a benzotriazole solution; dissolving a zinc source in methanol to obtain a zinc source solution; Dissolve 2-methylimidazole in methanol to obtain a 2-methylimidazole solution; S2. adding the benzotriazole solution to the zinc source solution to obtain a mixed solution; The 2-methylimidazole solution is added to the mixed solution, stirred, centrifuged, washed and dried to obtain the anti-corrosion filler, and then the obtained anti-corrosion filler is added to the coating raw material.

[0008] Optionally, in step S2, the ratio of the benzotriazole to the zinc source is 0.6-0.8:0.5-0.7.

[0009] Optionally, in step S2, the ratio of the 2-methylimidazole to the zinc source is 0.8-1.1:0.5-0.7.

[0010] Optionally, in step S2, the drying temperature is 60-80°C, and the drying time is 20-30h.

[0011] Optionally, the coating has a thickness of 85-95 μm.

[0012] Optionally, the coating material includes epoxy resin.

[0013] ZIF is a MOF material with a high specific surface area and porous structure, which can provide a large number of active sites to adsorb corrosion inhibitor molecules. At the same time, ZIF can effectively adsorb corrosion inhibitor molecules, maintain the stability of the corrosion inhibitor, and prolong its action time on the metal surface. The synthesis method of ZI is relatively simple, and different functional groups can be introduced through post-modification to further optimize its performance of loading corrosion inhibitors. Benzotriazole (BTA) is a corrosion inhibitor currently commonly used for corrosion protection of metal materials such as carbon steel. The N atom with a lone electron pair in the BTA molecule can form a coordination bond with the Fe atom, so that the BTA molecule is adsorbed on the surface of carbon steel to form a protective film; adding BTA@ZIF particles to the coating can, on the one hand, enhance the protective performance of the epoxy coating by sealing the pores in the epoxy coating, and on the other hand, the ZIF structure will collapse due to the pH change caused by the corrosion of the metal, releasing the corrosion inhibitor BTA to achieve protection of the metal.

[0014] The beneficial effects of the present invention are as follows: the preparation method is simple and convenient, and it is easy to realize large-scale production; the corrosion inhibitor has a high loading amount and can be controlled to be released after the corrosion reaction occurs, and the coating has an excellent self-repairing effect; the BTA@ZIF-8 particles have a high pyrolysis temperature, and there will be no problem of premature failure; BTA@ZIF-8 has good compatibility with the EP coating, the corrosion inhibition efficiency of BTA is high, and the self-repairing effect can be observed within 48 hours; BTA@ZIF-8 is easy to disperse in the coating, so the corrosion inhibition efficiency of the prepared coating is improved; it is convenient to quickly evaluate the self-repairing effect of the self-repairing coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 FT-IR images of BTA, ZIF-8 and BTA@ZIF-8; Figure 2 SEM images of BTA, ZIF-8 and BTA@ZIF-8; Figure 3Thermogravimetric curves of BTA, ZIF-8 and BTA@ZIF-8; Figure 4 The release curve of BTA in BTA@ZIF-8 over time; Figure 5 The immersion test results of BTA@ZIF−8 / EP coating and EP coating after immersion for 48 h, a is the immersion test result after immersion for 0.5 h, b is the immersion test result after immersion for 6 h, c is the immersion test result after immersion for 24 h, and d is the immersion test result after immersion for 48 h. DETAILED DESCRIPTION

[0016] The present invention is further described below through specific examples, but it should be pointed out that the specific material ratios, process conditions and results described in the embodiments of the present invention are only used to illustrate the present invention and cannot be used to limit the scope of protection of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention. Example 1

[0017] Take 0.7 g of BTA and dissolve it in 10 mL of methanol. Stir it magnetically to make it completely dissolved to obtain solution A. Take 0.6 g of zinc nitrate hexahydrate and dissolve it in 50 mL of methanol. Stir it magnetically to make it completely dissolved to obtain solution B. Take 1.0 g of 2-methylimidazole and dissolve it in 50 mL of methanol. Stir it magnetically to make it completely dissolved to obtain solution C. Solution A was quickly added to solution B and magnetically stirred for 10 min to obtain a mixed solution; Then, solution C was slowly added to the mixed solution and stirred at room temperature for 30 minutes. A white precipitate appeared and the mixture was centrifuged. The precipitate obtained by centrifugation was washed and placed in an oven at 70°C for 24 hours to obtain BTA@ZIF-8 particles, i.e., anticorrosive fillers.

[0018] The same preparation method as above was used except that solution A was not added to obtain ZIF-8.

[0019] The BTA@ZIF-8 particles, BTA, and ZIF-8 were characterized by Fourier transform infrared spectroscopy (FT-IR). Figure 1 shown.

[0020] Depend on Figure 1 It can be seen that ZIF-8 has a peak at 1579 cm −1 The characteristic peak at 421 cm is C=N of imidazole. −1 is the stretching vibration peak of Zn−N, 995cm −1 and 1145cm −1It is the C-N stretching vibration peak. 2500-3400cm in BTA −1 The N-H-H group causes continuous peaks. In the FT-IR spectrum of BTA, the C-C stretching vibration peak is at 1623 cm −1 1268cm −1 The stretching vibration peak of the C−H bond is at 1209 cm −1 At 740 cm −1 The FT-IR spectrum of BTA@ZIF-8 revealed that ZIF-8 −1 、1145cm −1 and 1579cm −1 The characteristic peaks of BTA at 740 cm −1 、2500-3400cm −1 In addition, the main characteristic peaks of BTA@ZIF-8 in the FT-IR spectrum are consistent with those of ZIF-8. This result shows that BTA has been successfully loaded onto ZIF-8.

[0021] The results of scanning electron microscopy (SEM) of ZIF-8 and BTA@ZIF-8 particles are shown in Figure 2. Figure 2 shown.

[0022] Depend on Figure 2 It can be seen that ZIF-8 has a rhombic dodecahedral crystal structure and a relatively uniform particle size with an average particle size of 0.14 μm. Compared with ZIF-8, the particle size of BTA@ZIF-8 has increased, with an average particle size of about 1.2 μm. This is mainly due to the inhibition of nucleation of ZIF-8 after loading with BTA, which leads to an increase in particle size. After loading with BTA, the particle surface is spherical, the surface becomes rough, and its surface has obvious cluster-like protrusions. This result shows that BTA has been successfully loaded on ZIF-8.

[0023] Thermogravimetric analysis of ZIF-8 and BTA@ZIF-8 particles showed that Figure 3 shown.

[0024] Depend on Figure 3It can be seen that the thermal stability of the corrosion inhibitor BTA is poor and it is completely decomposed at 273°C. At 130-610°C, the mass loss of ZIF-8 is about 6wt%, and the thermal weight loss at this stage is mainly caused by the volatilization of water and solvent on the surface. When BTA is loaded, the thermal weight loss of BTA@ZIF-8 at 130-610°C increases significantly. The thermal decomposition of BTA@ZIF-8 is mainly divided into three stages. At 25-130°C, the thermal weight loss of BTA@ZIF-8 is small, which is mainly caused by the volatilization of water and non-volatile solvent on the surface of the sample. At 130-610°C, the total thermal weight loss of the sample increases to 25wt%, which is mainly caused by the large amount of thermal decomposition of the corrosion inhibitor BTA. It is worth noting that the thermal decomposition temperature of the corrosion inhibitor BTA increases significantly, which is mainly due to the weak interaction between the carrier ZIF-8 and the corrosion inhibitor, which prolongs the thermal decomposition process of BTA. The third stage is 610-800℃, during which the thermal weight loss of BTA@ZIF-8 increases rapidly, which is mainly related to the collapse of the ZIF-8 skeleton structure. According to the difference in thermal weight loss between ZIF-8 and BTA@ZIF-8 at 610℃, the loading amount of BTA is 19wt%.

[0025] The BTA release performance of BTA@ZIF-8 was tested. The results are as follows Figure 4 shown.

[0026] Depend on Figure 4 It can be seen that with the extension of time, the concentration of BTA in the aqueous solution will increase, and its absorbance intensity will also increase (4a). In order to avoid the influence of the absorbance of ZIF-8, the wavelength of 278 cm −1 . According to different time periods at 278cm −1 The release curve of the corrosion inhibitor was obtained by comparing the absorbance intensity at pH = 5 with the standard curve. In the first 3 hours, BTA was released faster at pH = 5 and pH = 10, with the release amounts reaching 72.4% and 68.4%, respectively. At pH = 7, the release rate of BTA was slower, which prevented BTA from leaking during the coating curing process. This result shows that BTA@ZIF-8 can quickly realize the pH response to BI release.

[0027] Preparation of BTA@ZIF-8 self-healing coating A 10cm×10cm×0.5cm Q235 carbon steel was used as the substrate. The metal was polished with ink sandpaper, and then the surface oil was removed with ethanol and acetone. It was then dried with a hair dryer and set aside.

[0028] 1. Add BTA@ZIF-8 as filler to EP coating The self-healing coating containing BTA@ZIF-8 was prepared according to GB / T 20777-2006 "Inspection and preparation of paint and varnish samples". The specific steps are as follows: Weigh 11.4 g of bisphenol A diglycidyl ether, 7.3 g of neopentyl glycol diglycidyl ether and 11.4 g of polyetheramine curing agent respectively into a 250 mL beaker and perform ultrasonication for 30 min to make them dispersed evenly; 0.5 g of BTA@ZIF-8 particles were added to the above system and ultrasonically dispersed for 2 h to obtain a self-healing epoxy coating (i.e., BTA@ZIF−8 / EP coating); The self-repairing epoxy coating was evenly applied on the Q235 carbon steel after being polished by water-abrasive paper, and the coating was dried in a 50°C oven for 48 hours until it was completely cured, and the coating thickness was tested with a thickness gauge. The coating thickness was tested to be 90±5μm.

[0029] 2. BTA@ZIF-8 coating self-healing performance test The coating was prepared in the same manner as described above, except that BTA@ZIF-8 particles were not added, to obtain an EP coating.

[0030] The BTA@ZIF−8 / EP coating and EP coating were subjected to 48 immersion tests using artificially damaged coatings. Figure 5 shown.

[0031] Depend on Figure 5 It can be seen that after immersion for 0.5 h, the Nyquist curves of the two coatings both show a single capacitive reactance arc with similar capacitive reactance arc radius. At this time, the impedance values ​​of the two coatings are 6.68×10 4 Ω·cm 2 and 6.53×10 4 Ω·cm 2 The reason why the second capacitive arc was not observed is that the area of ​​electrochemical reaction at the coating / metal interface is very small, resulting in the time constant associated with the physical impedance of the coating and the time constant associated with the electrochemical reaction at the interface being of similar order of magnitude, overlapping and difficult to distinguish.

[0032] Depend on Figure 5 It can be seen that as the immersion time increases to 6 h, the impedance values ​​of the two coatings further decrease, and the radius of the capacitive reactance arc also decreases further, which is related to the rapid development of electrochemistry in the damaged area of ​​the coating. The impedance data at this time can still be fitted by the equivalent circuit B. The impedance values ​​of the two coatings are 5.66×10 4 Ω·cm 2 and 5.86×10 4 Ω·cm 2 As the immersion time was further extended to 24 h, the impedance values ​​of the two coatings were 3.28×10 4Ω·cm 2 and 3.08×10 5 Ω·cm 2 , the impedance value of the BTA@ZIF−8 / EP coating increased, but the impedance value of the EP coating further decreased with the extension of the immersion time. This is related to the rapid change of pH value in the damaged area of ​​the coating as the electrochemical reaction occurs, and the BTA@ZIF-8 particles added to the coating will collapse in response to the change in pH, releasing the corrosion inhibitor BTA to form a film on the metal surface to delay the invasion of corrosive particles into the metal surface.

[0033] Depend on Figure 5 It can be seen that as the immersion time increases to 48 h, the impedance value of the EP coating decreases to 4.68×10 4 Ω·cm 2 , an obvious diffusion tail appears in the Nyquist plot of the EP coating, indicating that the electrochemical reaction develops rapidly and a diffusion layer is accumulated on the metal surface. The impedance value of the BTA@ZIF-8 / EP coating increases to 4.31×10 5 Ω·cm 2 This may be related to the continuous release of corrosion inhibitor BTA. The results show that the BTA@ZIF-8 / EP coating has a good self-healing effect within 48 h.

Claims

1. A self-repairing epoxy coating loaded with corrosion inhibitor ZIF-8 particles, comprising an anti-corrosion filler added to a coating raw material, characterized in that: The anticorrosive filler comprises a zeolite imidazole ester framework loaded with benzotriazole, and the average particle size of the zeolite imidazole ester framework loaded with benzotriazole is 1-1.5 μm.

2. The self-repairing epoxy coating according to claim 1, characterized in that: The zeolite imidazole ester framework loaded with benzotriazole is spherical.

3. The self-repairing epoxy coating according to claim 2, characterized in that: The coating has a thickness of 85-95 μm.

4. The self-repairing epoxy coating according to claim 3, characterized in that: The coating material includes epoxy resin.

5. The method for preparing the self-repairing epoxy coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. dissolving benzotriazole in methanol to obtain a benzotriazole solution; dissolving a zinc source in methanol to obtain a zinc source solution; dissolving 2-methylimidazole in methanol to obtain a 2-methylimidazole solution; S2. Add the benzotriazole solution to the zinc source solution to obtain a mixed solution; add the 2-methylimidazole solution to the mixed solution, stir, centrifuge, wash, and dry to obtain the anti-corrosion filler, and then add the obtained anti-corrosion filler to the coating raw material.

6. The preparation method according to claim 5, characterized in that: In step S2, the ratio of the benzotriazole to the zinc source is 0.6-0.8:0.5-0.

7.

7. The preparation method according to claim 5, characterized in that: In step S2, the ratio of the 2-methylimidazole to the zinc source is 0.8-1.1:0.5-0.

7.

8. The preparation method according to claim 5, characterized in that: In step S2, the drying temperature is 60-80°C, and the drying time is 20-30 hours.

Citation Information

Patent Citations

  • Preparation method of corrosion inhibitor loaded BTA-ZIF-8 composite powder

    CN115073956A

  • Preparation method of self-repairing anti-corrosion coating based on ZIFs

    CN116004086A

Cited By

  • Ti3C2Tx-coated SiO2-BTA-coated ZIF composite material, preparation method, composite coating and application

    CN122188438A